Ekonomiczne i społeczne uwarunkowania rozwoju klasy średniej w Polsce w aspekcie historycznym - Konopska-Struś, Emilia (Historical Aspect of Economic and Social Conditions of Middle Class Progress in Poland, 2008)
The middle class is not explicitly defined in literature. Nowadays, the division into the old and the new middle class prevails. The old middle class is based on small and medium-sized enterprises. The new middle class or knowledge class consists of free occupation representatives, managers and people whose capital is their knowledge. In Poland the middle class forming process was interrupted by the second World War and next, by the transition to centrally planned economy. In consequence, it led to the reduction of small and medium-seized enterprises importance, which were a stem of the middle class at that time. The next chance for the middle class rebirth appeared at the beginning of the 90s of the 20th cen- tury. However, the expansion of the private enterprises was hindered by the lack of institutional resolution, restrictive tax package, as well as insufficient government and banks financial support. The phenomena mentioned above was a reason why the middle class in Poland did not come into being in such a form as in Western Europe, which was negative, because the middle class guarantees the political and economic stabilization of the country.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 244-258